ENZYMOTHERAPY IN PEDIATRIC PRACTICE: PROBLEMS AND SOLUTIONS - S.K. Arshba (Union of pediatricians of Russia, 2009)
This article reviews possibilities of enzyme medicine usage with pancreas malfunctions and gastrointestinal tract motility disorders in children. The authors also call readers' attention to possible causes of malfunctions, clinical aspects and key diagnostic methods of the pathology.Key words: pancreas, gastrointestinal tract, malfunction, enzymotherapy, children.